Evaluation of Nurses' Practices toward the Control of Patients’ Complications at the Respiratory Care Unit in Baghdad Teaching Hospitals - abed, Humam; Kadhim, Haleema (Iraqi National Journal of Nursing Specialties, 2014)
Objective(s): To evaluate nurses' practices who work in respiratory intensive care units to control thecomplications of patients admitted at this unit and determine the relationship between nurses' sociodemographiccharacteristics and their practices.Methodology: A descriptive study was carried out at Respiratory Care Unit at Baghdad teaching hospitals thatstarted from February 22th, 2013 to August 30th, 2013. A purposive "non-probability" sample of (70) nurses whowork in Respiratory Care Unit was selected from Baghdad teaching hospitals. The data were collected through theuse of constructed questionnaire that consists of two parts; (l) Demographic data form that consists of 7items and(2) nurses' practice form that consists of 4sections (112) items. Data were collected by means of direct observationtechnique with the nurses. The reliability of the questionnaire was determined through a pilot study that wascarried out through the period from January 6th 2013 through February 10th 2013.Descriptive statistical measures(frequency, percent, mean of score, Standard deviation and Weighted mean) and inferential statistical (Regression)was used for the data analysis.Result: The findings of the study indicated that there is a practice deficit of Respiratory Care Unit nurses in someaspects relative to control of patient complication. significant relationship was found between nurses' practice andtheir (age, gender, marital status, level of education, Years of working in nursing, Years of working in RCU,Participation in training courses, Number of training courses related to RCU, Place of training courses in RCU,Duration of training courses in RCU, and in Respiratory Care Unit Nurses' practice to control of patientcomplication in Respiratory Care Unit.Recommendations: The researchers recommend that special training session, concerning patient complication andstandard Respiratory Care Unit nurse practice toward patient complication that should be followed in RespiratoryCare Unit wards and booklets should be designated and presented to all Respiratory Care nurses.